Pengaruh Latihan Sirkuit terhadap Kemampuan Panjat Tebing Kategori Lead pada Mahasiswa Pencinta Alam Universitas PGRI Palembang - Wahyu Herman; Ramanata Disurya; Daryono Daryono (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
The problem with this research was that athletes did not have maximum endurance in climbing the lead climbing technique. The aim of the research is to influence circuit training on the lead category rock climbing abilities of students who love nature at Pgri University in Palembang. The research method is an experimental one group pretest-posttest design technique. The research population consisted of 7 people and the sample was the total population. Data were collected using tests, with endurance test instruments for athletes using the lead climbing technique. Data analysis used paired sample t test SPSS 16. The results of the research stated that there was an influence of circuit training on the rock climbing ability of the lead category among students who love nature at Pgri Palembang University because Tcount>TTable (6.810 > 1.83)